Severe water intoxication and secondary depressive syndrome in relation to delusional infestation - Lai J; Lu Q; Xu Y; Hu S (Neuropsychiatric Disease and Treatment)
Jianbo Lai,1 Qiaoqiao Lu,1 Yi Xu,1,2 Shaohua Hu1,2 1Department of Psychiatry, First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China; 2The Key Laboratory of Mental Disorder’s Management in Zhejiang Province, Hangzhou, People’s Republic of China Abstract: This study presents a case of severe water intoxication in a female patient with delusional infestation. Self-induced excessive water ingestion is a rare medical condition, which has not been reported in patients with delusional infestation yet. The patient in this case study was a 60-year-old Chinese woman, who was admitted to our hospital because of a feeling of skin infestation. She suffered from loss of consciousness and generalized tonic–clonic seizure after drinking 12 L of water during bowel cleansing before colonoscopy. Sufficient laboratory and imaging examinations were performed to exclude other possible causes of severe hyponatremia, such as hypothyroidism, diabetes insipidus, and syndrome of inappropriate antidiuretic hormone. Besides, the cystic lesion in the posterior pituitary revealed by cranial magnetic resonance imaging was not accountable for her delusional symptoms as well as excessive drinking behavior. Her delusional symptoms were in complete remission with a combination of risperidone and aripiprazole. However, nearly 3 months after discharge, this patient suffered from depressed mood and was diagnosed with depressive syndrome, and even attempted suicide. This case highlights the possibility of self-induced water intoxication in patients with delusional infestation, inevitably adding to the complexity of the disease, and indicates the necessity of precautions for secondary psychotic or mood problems after symptomatological remission. Keywords: delusional infestation, depressive syndrome, suicide, water intoxication